Polygamy (Ta'addud Az-Zaujat) in the Perspective of Critique of Interpretation Between Normative Ideals and Social Reality - Fauzan Sugiyono; Ahmad Faiz Al-Hakam (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2025)
Polygamy (taʿaddud az-zaujāt) is a controversial issue in Muslim society, both from a social perspective and within Islamic law. Although this practice has a basis in the Qur'an, particularly Surah An-Nisa': 3 and Surah An-Nisa': 129, its interpretation continues to spark debate between classical exegetes and contemporary thinkers. The dominant critique of this verse tends to be literal and legal-formal, legitimizing polygamy as a form of absolute permissibility, without delving deeper into the meaning of the Qur'an's requirements for justice. As a result, the practice of polygamy in society often leads to gender injustice, unequal marital relations, and psychological and social burdens for women and children. The purpose of this study is to analyze the rationale of classical and modern exegetes regarding the differing legal views on polygamy and to evaluate the construction of classical normative thought to make it more holistic, empathetic, and in line with contemporary realities and the values of the maqasid sharia (the principles of Islamic law) in marriage. This study is a library research study using a descriptive analytical comparative method between classical and contemporary interpretations through a qualitative and social contextual approach. The results of this study indicate three differing views of commentators regarding the law of polygamy, each with its arguments: one group holds that polygamy is an absolute recommendation; the other holds that the recommendation is a conditional emergency; and the third rejects polygamy and even discourages it due to its numerous harms. Monogamy is a fundamental principle of marriage (munakahat) in Islam.